Pemanfaatan Tepung Ubi Jalar Ungu (Ipomoema batatas) dan Tepung Wortel (Daucus carota L) Untuk Meningkatkan Kecerahan Warna dan Pertumbuhan Ikan Mas Koki (Carassius auratus) - Tamar Mustari; Wardha Jalil; Aprilia Rahman (AquaMarine (Jurnal FPIK UNIDAYAN ), 2022)
Goldfish (Carassius auratus) is a type of ornamental fish with attractive color variations ranging from red, yellow, white, orange, black and silver. The color in fish is caused by the presence of pigment cells or chromatophores which are found in the dermis on the scales, outside and under the scales. This study aims to determine the effect of sweet potato flour (Ipomoema batatas) and carrot flour (Daucus carota L) on the color brightness and growth of goldfish. The research was conducted for 50 days, at the Fish Seed Production Laboratory of FPIK Unidayan. The rearing medium uses clear plastic jars with a volume of 5 liters, totaling 12 pieces which are equipped with aeration and filter installations. The test animals were 60 goldfish seeds measuring 5-7 cm. The test feed is in the form of pellets with the main raw materials of sweet potato flour and carrot flour. The research design used a completely randomized design with 4 treatments and 3 replications. The treatment were A (45% carrot flour), B (15% purple sweet potato flour and 30% carrot flour), C (30% purple sweet potato flour and 15% carrot flour) and D (45% purple sweet potato flour). The results showed that the addition of sweet potato flour and carrot flour to commercial feed had no significant effect on color change and growth. The water quality values obtained during the study were at a proper level for the growth of goldfish.